Integrated farming of crops and livestock: effects on cashew farming income in Sumenep Regency - Moh. Alif Al Farisyi; Dwi Ratna Hidayati; Nor Qomariyah (Agriekonomika, 2025)
The integration of crops and livestock is a common practice in agriculture, particularly within the cashew farming sector. This approach supports the efficient use of limited land resources and promotes sustainable agricultural development.  Nevertheless, its economic implications for farmers warrant closer investigation. This study was conducted to examine the relationship between integrated farming practices and farm income in Sumenep District, East Java Province. The analysis employed the 4F framework (food, feed, fuel, and fertilizer) as the basis for integrated farming practice. The study used a quantitative approach. A total of 40 farmers were collected for the study and analysed using frequency distribution, income analysis, and the Chi-Square test). Most farmers applied the 3F system, with two variations: food–feed–fertilizer and food–fertilizer–fuel. An average income was Rp 24,369,217 per hectare, however, the majority of farmers reported income levels below Rp 5 million. The Chi-Square analysis revealed a statistically significant association between the implementation of integrated farming (through the 4F framework) and the income of cashew farmers. Further intervention is needed to strengthen integrated farming practices in order to improve farmers’ income.